The emergence and development banks: historical retrospektive - Тришак, Л. С. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article deals with the historical aspects of the genesis of banks subject to the requirements of the principle of historicism - one of the elements of the dialectical method of cognition phenomena and processes. Based on historical and economic literature the theoretical analysis of the origin and development banking, highlights and summarizes theoretical views on the formation of Ukrainian economics of the system. The main stages in the evolution of banks and banking. It has been proved that many problems in banking, as history shows, at various times were similar, so studying this experience will help avoid a repeat of past shortcomings in the future. On the basis of the study found that the need for advanced functioning, efficient banking system due to the evolution of financial and credit relations. Results of the study historical aspects of banking have shown that the development of an effective banking system in Ukraine in order to avoid negative errors affecting the economic development of the country for any changes in the theory and practice of banking, it is advisable to consider the most historical aspects to avoid old mistakes and shortcomings.